STUDENT CLUSTER ANALYSIS AS AN EFFORT TO OPTIMIZE CAMPUS PROMOTION - Aulia, Romy; Khomarudin, Agus Nur; Laksmana, Indra; Jamaluddin, Jamaluddin; Novita, Rina (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: This research tries to describe student cluster analysis, as an effort to optimize campus promotion to various schools and regions. It is known that every year, Politeknik Pertanian Negeri Payakumbuh, abbreviated as PPNP, brings in students from various regions in Indonesia. Regarding the campus promotion strategy process, the PPNP promotion section has not been based or referred to the results of processing existing student data. So that the budget used by the campus promotion team has not been right on target with the results of students who can be brought to campus. In addition, the existing student database has not been processed or explored further, so that it has not produced knowledge that is very useful as material to support the decisions of the academic and student affairs department and the campus promotion team. The method used in this research is CRISP-DM which stands for Cross- Industry Standard Process for Data Mining. Based on the characteristics of each cluster, the PPNP Promotion Team in conducting the next socialization is advised to prioritize provinces such as West Sumatra and North Sumatra. Currently, managerial circles in this context, university leaders are expected to be able to make data-based decisions. Data-based decision making can foster a culture of sustainable innovation, produce customer-centric offerings and drive long-term business growth.            Keywords: cluster analysis; student data; k-means clustering; campus promotion  Abstrak: Penelitian ini mencoba untuk mendeskripsikan analisis cluster mahasiswa, sebagai upaya optimalisasi dalam melakukan promosi kampus ke berbagai sekolah dan daerah. Diketahui bahwa setiap tahunnya, Politeknik Pertanian Negeri Payakumbuh disingkat PPNP mendatangkan mahasiswa dari berbagai daerah di Indonesia. Terkait dengan proses strategi promosi kampus, bagian promosi PPNP belum didasarkan pada hasil pengolahan data mahasiswa yang ada. Sehingga anggaran yang digunakan tim promosi belum tepat sasaran dengan hasil mahasiswa yang dapat didatangkan ke kampus. Selain itu database mahasiswa yang ada selama ini belum diolah atau digali secara jauh, sehingga belum menghasilkan pengetahuan yang bermanfaat sebagai bahan untuk mendukung keputusan bagian akademik dan kemahasiswaan serta tim promosi kampus. Metode yang digunakan dalam penelitian ini yaitu CRISP-DM merupakan singkatan dari Cross-Industry Standart Process for Data Mining. Berdasarkan karakteristik setiap cluster, maka untuk Tim Promosi PPNP dalam melakukan sosialisasi berikutnya disarankan memprioritaskan pada provinsi seperti Sumatera Barat dan Sumatera Utara. Saat ini kalangan manajerial yaitu pimpinan perguruan tinggi diharapkan dapat melakukan pengambilan keputusan berbasis pada data. Pengambilan keputusan berbasis data dapat menumbuhkan  budaya  inovasi  yang berkelanjutan, menghasilkan penawaran yang berpusat pada pelanggan dan mendorong pertumbuhan bisnis jangka panjang. Kata kunci: analisis cluster; data mahasiswa; k-means clustering, promosi kampus